Comparing the fertility of soils under Khaya ivorensis plantation and regenerated degraded secondary forests - Yetti Heryati,; Abdu, Arifin; Mahat, Mohd Noor; Abdul Hamid, Hazandy; Jusop, Shamshuddin; Nik Ab. Majid, Nik Muhamad; Heriansyah, Ika; Ajang, Leslie; Ahmad, Khairulmazmi (Science Publications, 2011)
Problem statement: It is widely accepted that conversion of natural forest to other land use types leads to deterioration of soil fertility and increased soil compaction which consequently become degraded secondary forests. Degraded secondary forest or forestland is indicated by low in soil fertility and organic matter due to imbalance input and output from original vegetation. Forest plantation through planting fast growing exotic species is usually implemented to curtail degradation of secondary forest or forestland and improve the soil fertility through organic matter accumulation. However, fundamental information on degraded forestland being converted to forest plantation using exotic species such as Khaya ivorensis is not available. The objectives of this study were: (1) to characterize the properties of three degraded soils under rehabilitation using K. ivorensis; and (2) to evaluate their fertility status by Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF). Approach: This study was concentrated on three soil series (Rengam, Durian and Padang Besar) found under K. ivorensis plantation and at the adjacent secondary forest in Segamat, Johor, Malaysia. To characterize and evaluate the soil fertility status for each soil series, three plots (30 x 40 m) were randomly established on each soil series. Soils for each series were sampled at the depth of 0-10 cm (surface soil) and 20-30 cm (subsurface soil). They were randomly collected at six different points for each replicate. Soil analyses were carried out accordingly. Results: The soils both in planted and secondary forests were moderately acidic to slightly acidic with low content of exchangeable bases and available P but high in Al saturation. The Rengam series under K. ivorensis plantation contained higher total carbon and clay compared with those of Padang Besar and Durian series. Clay and total carbon contents were highly correlated with the Cation Exchange Capacity (CEC), indicating the potential of negative charge produced by the clay and organic playing an important role in supplying and holding plant nutrients. The SFI result revealed that soil fertility status of Rengam soil was significantly higher than the other two soil series. There was no significant difference observed for SEF. Based on SFI and SEF values, there were no significant differences of fertility status between the planted and secondary forests for both soil depths. Conclusion: This study revealed that Rengam soil is more fertile than the other two soils. Using SFI and SEF it can be concluded that fast growing exotic species of K. ivorensis has the potential to improve site productivity and soil fertility.